The Intersection of the Progressive Law Theory and the Self-Declaration Concept of MSEs Halal Certification - Akhmad Khalimy; Yusriyadi Yusriyadi; Ro'fah Setyowati; Syahruddin Syahruddin; Abdul Muizz Abdul Wadud (Journal of Indonesian Legal Studies, 2023)
The self-declaration by Small Micro Enterprises (MSEs) for obtaining a halal logo has both advantages and disadvantages. Proponents argue that self-declaration makes it easier for MSEs to acquire a halal certificate, reduces the submission period, and streamlines the certification process. However, opponents argue that self-declaration violates certain laws, such as the UUJPH and the Consumer Protection Act. The Omnibus Law (UUCK) conceptually includes halal in the licensing cluster to facilitate business, but the Constitutional Court has deemed UUCK formally flawed and conditionally unconstitutional. Self-declaration simplifies the licensing process for obtaining a halal certificate specifically for SMEs. It waives certification fees, reduces processing time, and simplifies aspects of business licensing. MSEs can obtain a free certificate through self-declaration if their products meet certain conditions, including not being at risk, being made from natural ingredients, being halal, having a simple production process, having assistance with Halal Production Process (PPH), and being supported by an MUI fatwa. Progressive law recognizes that the law is not absolute or final, but an evolving process aimed at achieving justice and improving human lives. This article explores the intersection between self-declaration and Satjipto Raharjo's progressive legal theory. It highlights the shared objectives of realizing justice, assisting MSEs in obtaining halal certification, humanizing the law, facilitating licenses for MSEs, and adapting regulations to societal changes. The approach encourages breaking and making rules to create progressive laws and involves business actors and companions in the halal certification process, making the law responsive and participatory.